ACE2 in the Era of SARS-CoV-2: Controversies and Novel Perspectives - Saponaro, Federica; Rutigliano, Grazia; Sestito, Simona; Bandini, Lavinia; Storti, Barbara; Bizzarri, Ranieri; Zucchi, Riccardo (Frontiers in Molecular Biosciences, 2020)
Angiotensin-converting enzyme 2 (ACE2) is related to ACE but turned out to counteract several pathophysiological actions of ACE. ACE2 exerts antihypertensive and cardioprotective effects and reduces lung inflammation. ACE2 is subjected to extensive transcriptional and post-transcriptional modulation by epigenetic mechanisms and microRNAs. Also, ACE2 expression is regulated post-translationally by glycosylation, phosphorylation, and shedding from the plasma membrane. ACE2 protein is ubiquitous across mammalian tissues, prominently in the cardiovascular system, kidney, and intestine. ACE2 expression in the respiratory tract is of particular interest, in light of the discovery that ACE2 serves as the initial cellular target of severe acute respiratory syndrome (SARS)-coronaviruses, including the recent SARS-CoV2, responsible of the COronaVIrus Disease 2019 (COVID-19). Since the onset of the COVID-19 pandemic, an intense effort has been made to elucidate the biochemical determinants of SARS-CoV2-ACE2 interaction. It has been determined that SARS-CoV2 engages with ACE2 through its spike (S) protein, which consists of two subunits: S1, that mediates binding to the host receptor; S2, that induces fusion of the viral envelope with the host cell membrane and delivery of the viral genome. Owing to the role of ACE2 in SARS-CoV2 pathogenicity, it has been speculated that medical conditions, i.e., hypertension, and/or drugs, i.e., ACE inhibitors and angiotensin receptor blockers, known to influence ACE2 density could alter the fate of SARS-CoV-2 infection. The debate is still open and will only be solved when results of properly designed experimental and clinical investigations will be made public. An interesting observation is however that, upon infection, ACE2 activity is reduced either by downregulation or by shedding. These events might precipitate the so-called “cytokine storm” that characterizes the most severe COVID-19 forms. As evidence accumulates, ACE2 appears a druggable target in the attempt to limit virus entry and replication. Strategies aimed at blocking ACE2 with antibodies, small molecules or peptides, or at neutralizing the virus by competitive binding with exogenously administered ACE2, are currently under investigations. In this review, we will present an overview of the state-of-the-art knowledge on ACE2 biochemistry and pathophysiology, outlining open issues in the context of COVID-19 disease and potential experimental and clinical developments.